Bilateral thoracic radiographs increase lesion detection in horses with pneumonia or pulmonary neoplasia but do not bring any additional benefit for inflammatory or diffuse pulmonary disease. Issue 5 (11th April 2022) - Malek, Gwladys; Leclere, Mathilde; Masseau, Isabelle; zur Linden, Alex; Beauchamp, Guy; Finck, Cyrielle
Abstract: Published studies describing the effects of bilateral radiographic projections on the detection of equine pulmonary lesions are currently lacking. The objectives of this retrospective, single center, observational study were to compare unilateral and bilateral thoracic radiographic projections for the detection of pulmonary lesions in a group of horses. Based on their clinical diagnosis, 167 adults and foals with bilateral thoracic radiographs were classified as having pneumonia (n = 88), inflammatory or diffuse pulmonary disease (n = 72), and pulmonary masses (n = 7). After an initial interrater repeatability test, right‐to‐left and left‐to‐right projections were anonymized and independently interpreted by a radiologist blinded to the clinical diagnosis. Scores were attributed for each pattern/lesion (alveolar, interstitial, bronchial, nodules/masses, cavitary lesions) and each quadrant. Agreement between scores from each projection was evaluated with Bland–Altman plots. Lesions identified on one side but not on the contralateral projection were considered discordant. There was no preferential lateralization of pulmonary lesions. The prevalence of discordance was 14.4%, 9.0%, and 4.2% for alveolar pattern, nodules/masses, and cavitary lesions, respectively. Up to nine horses (10.2%) with pneumonia could have been misdiagnosed. A pulmonary mass would have been missed in one case. For inflammatory or diffuse disease, discordance was slight, and the addition of contralateral projections had no impact on radiographic interpretation. In conclusion, in horses with pneumonia or neoplasia, bilateral projections, or adding at least one contralateral caudoventral view, increased the probability of identifying pulmonary lesions. In horses with inflammatory or diffuse disease, bilateral thoracic radiography provided no additional benefit.